WORLD WAR I. THE OTHER FACE OF THE WAR - BOLOVAN, Ioan; GRÄF, Rudolf; HEPPNER, Harald; TĂMAȘ, Oana Mihaela (2016)
“THE OTHER FACE of the war” indicates there are some need to focus on World War I, which had a great impact on later generations influencing not only the interwar period, but also some thinking and acting till nearpresent.“The other face of the war” symbolizes also the readiness to study not only the military but also the civil aspects including the perspectives of the contemporaries on the other sides of the fronts.“The other face of the war” may also show the respect to all small contemporary people too involved unwillingly into a period of dense violence.Finally “the other face of the war” means the reason to participate at an international discussion on World War I Studies focusing on less known subjects for working in favour of a larger horizon.